Precise Excitation of a Switched Reluctance Machine under Regenerative Mode in High-Speed Operation - Riyadi, Slamet; Pratomo, Leonardus Heru (International Journal on Engineering Technology, 2024)
The implementation of electric machines in electric and hybrid electric vehicles offers some advantages, including the ability to operate in regenerative mode. Switched reluctance (SR) machines have been alternative solutions due to their characteristics. Operating an SR machine in propulsion mode requires high torque and minimal torque ripple, while producing optimal output power in regenerative mode is required. In high-speed operation, when the back electromotive force is greater than the DC link voltage, single pulse-based methods are often used. Torque ripple problems can be neglected due to rotor inertia. In this paper, a single pulse-based control for SR machines in high-speed operation under regenerative and discontinuous conduction modes is analyzed. Excitation to magnetize the rotor and generation process to produce output power are compared to determine the effectiveness of energy saving during regenerative mode. By using a simple control strategy, precise excitation angles can be obtained to turn the machine on and off. Experimental work has been done to support the analysis. They show that by using proper excitation angles, the optimal output power can be generated.